PERANCANGAN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB DAN SMS GATEWAY DI SMA NEGERI 3 PADANG - Fitri Yanti; Yasdinul Huda; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
Senior High School number 3 in Padang is International Standard School Stubs, which began seriously in optimizing library information system in order to improve competence. Witg the developments of information system book online library that uses PHP and SMS Gateway can make it easier for members to borrow of books. The library information system can also facilitate admin in arranging the books, borrowing, repayment and fines are all done by DBMS. In order to get accurate and precise reports. Hopes that there is this system can be a reference and cover all problems that exist in the library Senior High School number 3 in Padang.   Keywords: Library Information System, Books, SMS Gateway